The relationship of appreciation of Self - Esteem and the performance of some of the basic skills to young players for handball - م.م. لقاء عبد الزهرة أ.د إسراء فؤاد أ.د سعاد سبتي (physical education and sport sciences college for women/ Baghdad University, 2018)
The aim of the study to identify the level of appreciation of self-esteem, and the level of performance of some of the basic skills to young players for handball, identify the relationship of Self - Esteem the performance of some of the basic skills to young players for handball, and used the researcher research approach descriptive relationship style on a sample young players for handball of (24) a player with (32.432%) of community of (74) randomly selected, was also selected (20), the player for the foundations of scientific transactions of the standard self-esteem, and identify the type of the appropriate measure of target sample and foundations scientific transactions him and handling skills, receipt and corrigendum and deterrence, defense for handball, after the application of the gauge and skill tests in the time period from 29/2/2016 to 10/3/2016, and was addressing the results pouch system Statistical Commission (SPSS), The researcher concluded that the young players for handball have clear appreciation of their self-esteem, is linked to the Self - Esteem of the positive performance of the basic skills and three young players for handball, the greater the Self - Esteem whenever the improved performance of the basic skills and three young players for handball